Propuesta de mejora del proceso productivo de la línea de plancha de fibrocemento de la Fábrica Peruana Eternit S.A. - Garcia Quispe, Marco Antonio (2019)
The thesis has as a general objective to demonstrate that it is feasible to improve the production process of the fiber cement sheet line of the Peruvian Eternit Factory using industrial engineering tools. Through technical, economic and social justifications itwas determined that it is feasible to comply with the general objective set.